Soviet Life: neuvostoliittolainen perhelehti amerikkalaisille. - Kinturi, Marja-Liisa. (1982)
Soviet Life - a Russian family magazine for Amaricans.
Summary: Soviet Life - a Russian family magazine for Amaricans.
Keywords: aikakauslehdet; tidskrifter